2002
DOI: 10.1021/bi011970h
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Cytoplasmic Dynein Light Chains Tctex-1 and LC8 with the Intermediate Chain IC74

Abstract: The interactions of three subunits of cytoplasmic dynein from Drosophila melanogaster, LC8, Tctex-1, and the N-terminal domain of IC74 (N-IC74, residues 1-289), were characterized in vitro by affinity methods, limited proteolysis, and circular dichroism spectroscopy. These subunits were chosen for study because they are presumed to promote the assembly of the complex and to be engaged in the controlled binding and release of cargo. Limited proteolysis and mass spectrometry of N-IC74 in the presence of LC8 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
127
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(140 citation statements)
references
References 41 publications
8
127
0
Order By: Relevance
“…Previous work revealed that LC8 binds to DIC 29,30 , but the binding partner of Arl3 is unknown. To examine whether Arl3 binds either dynein, dynactin or LC8, we performed glutathione S-transferase (GST) pull-down assays using Arl3-conjugated beads.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work revealed that LC8 binds to DIC 29,30 , but the binding partner of Arl3 is unknown. To examine whether Arl3 binds either dynein, dynactin or LC8, we performed glutathione S-transferase (GST) pull-down assays using Arl3-conjugated beads.…”
Section: Resultsmentioning
confidence: 99%
“…There does not seem to be a family member in Saccharomyces cerevisiae. There are also other DLC families that bind to DIC, including Tctex-1/LC14, Tctex-2/LC2, LC6, and LC8/PIN (Bowman et al, 1999;King, 2000;Makokha et al, 2002). Of these other DLCs that bind to the DIC, Tctex-1 and LC8 have been shown to function as motor receptors to link cargo to the motor machinery (Almenar-Queralt and Goldstein, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Of these other DLCs that bind to the DIC, Tctex-1 and LC8 have been shown to function as motor receptors to link cargo to the motor machinery (Almenar-Queralt and Goldstein, 2001). Although Tctex-1 and LC8 share limited sequence identity, both bind a number of unrelated cargo in a similar manner (Mok et al, 2001;Makokha et al, 2002). Similarly, these DLCs are only 8 and 14% identical to mLC7-1, respectively.…”
Section: Molecular Biology Of the Cell 4486mentioning
confidence: 99%
“…It is generally admitted that the light chain portion is engaged in cargo binding and attached to cell organelles (e.g. mitochondria) while contributing to their localization (Makokha et al, 2002;Mok et al, 2001;Williams et al, 2005). Schwarzer et al (2002) reported that DYNLT1 slightly increases the voltage-dependence of VDAC1, indicating that DYNLT1 has the ability to modulate channel properties.…”
Section: Discussionmentioning
confidence: 99%